CAPABILITIES OF SCRATCH FOR WORKING WITH ANIMATIONS - Bagbekova Laylo; Djumaniyazova Malika (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the importance of Scratch technology in education, creation of animated and interactive projects, cartoons and other multimedia products in the Scratch programming environment, ease of use, interface and capabilities of the working environment in the Scratch visual program for students of any age.